Kemanusiaan dalam Hukum Keimigrasian: Tinjauan Terhadap Perlindungan Anak dalam Kasus Pengungsi - Flaventiano Alo Labertho Ohei; Sri Kuncoro Bawono; Catur Susaningsih (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
In an ever-evolving global context, immigration law has emerged as a prominent concern within the discourse of human rights. This article delves into the significance of humanity within immigration law, particularly in safeguarding refugee children. Immigration law, as a complex and diverse field worldwide, must steadfastly uphold the principle of humanity as its cornerstone. This principle underscores that the fundamental rights of every individual, regardless of their immigration status, should be respected and protected by nations and the international community. The protection of children within immigration law encompasses various aspects, including access to education, healthcare, family reunification, and the prevention of exploitation and violence. International organizations such as UNICEF play a pivotal role in promoting and overseeing the safeguarding of refugee children, including humanitarian principles. Concluding this discourse, it is essential to remember that protecting children in refugee cases is a true test of the principles of humanity within immigration law. It assesses the ability of nations and the international community to act in accordance with the fundamental values of humanity they adhere to. Therefore, it is crucial to continually raise awareness regarding the protection of refugee children, enhance existing immigration policies, and ensure that refugee children receive protection in line with their human rights.